Growth and survival : an ecological analysis of court reform in urban China / Jonathan J. Kinkel, Arizona State University. - Kinkel, Jonathan J. (Cambridge University Press, 2022)
Bridging disparate literatures on courts and the legal profession in China, Jonathan J. Kinkel introduces an innovative cross-disciplinary framework to understand the reality of Chinese politics and society. Fusing a variety of perspectives from social ecology, historical institutionalism, and empirical legal studies, Kinkel contextualises patterns of court reform within China's rapid economic and social transformations. This book's extensive case studies emphasise the dynamic expansion of the legal system in the post-Mao reform period and demonstrate that law firm growth in large cities, especially in the early twenty-first century, pressured courts at the local and national levels to enhance judicial autonomy. Advancing debates on the multiplicity of political-legal regimes, this book offers a comprehensive, empirical account of how reforms in both the public and private arenas can interact and operate alongside one another.